اندلس میں مسلم حکمرانی کا دور زوال:چند اہم فقہی مباحث کا مطالعہ - ڈاکٹر تنویر احمد (FIKR-O NAZAR فکر ونظر, 2012)
The Muslim eight centuries rule over the Iberian Peninsula (711-1492) began to totter in the eleventh century and finally came to an end with the fall of Granada. During this age of the decline of Muslim rule, large Muslim population and settlements in the Iberia continually fell under the rule of northern Christian states. This new political configuration of the land brought a series of serious challenges to the Muslim population of these newly conquered lands. Among these challenges, a few were of (fiqhi) nature. The juristic response to this situation was reflected in fatawas and such other juristic correspondences that were either lost or remained unpublished until recent times. With the growing interest in the current Muslims presence in the West, some of these materials have been unearthed and published. Although the newly retrieved materials do not give the detailed account of the fiqhi debates that became current in those times yet these are helpful to identify the main features of these debates. The present article is an attempt to this direction.